Examination of Physical Properties and Morphological Characteristics of Cell-Free Matrix of Vascular-Valve Bioprosthesis - Popandopulo, Andrey G.; Petrova, Marina V. (Problems of Cryobiology and Cryomedicine, 2013)
N/A Probl Cryobiol Cryomed 2013; 23(3):275–278.